The Implementation of Blended Learning in Teaching Reading - Afi Normawati (English Education Department - Universitas Nasional Karangturi, 2021)
In this rapidly transforming way of teaching, blended learning has become popular across all education levels as it integrates the advantages of traditional classroom activities with online digital media. In the context of teaching English as a foreign language, teachers need to adapt to the use of technology in their teaching activities so that the learning objectives can be achieved successfully. This paper describes the implementation of blended learning in the Engagement Reading class conducted in the English Language Education Department of Universitas Nasional Karangturi. To get the data, the researcher conducted observation, interview, and documentation. The result of the study shows that the stages of building knowledge of the field, modeling of the text, joint construction of the text, and independent construction of the text are applied in the reading class. To facilitate the teaching and learning process, Google Classroom, WhatsApp, Zoom, Mozilla Firefox, and Chrome are utilised. At the end of the course, the students have positive perception toward the implementation of blended learning in the reading class. This is because they feel that the use of technology in blended learning facilitates communication and interaction, engagement, and collaboration. However, they still have problem commonly faced by the students in Indonesia, which is internet connection and credit quota.